A Fast Calculation Method of Parasitic Inductances in the Bus Circuit of Double- IGBT Module Based on Double-pulse Experiment - HU Zhenqiu; PENG Zaiwu; HUANG Xuanfang; YIN Zhigang; HUANG Yishan (Kongzhi Yu Xinxi Jishu)
Voltage spike suffered by double-IGBT module will lower the current that system can control and pull down the safety threshold, which restricts the control scheme to be used. The overvoltage is determined by the parasitic inductances in the circuit. In order to control this parameter at the initial period of system design, it is necessary to figure out a method to calculate the parasitic inductances. In this paper, it presented a fast calculation method for the parasitic inductances of double-IGBT module bus circuit, which uses the turnoff waveform of double-pulse experiment. Only a small amount of data is needed to calculate the parasitic inductances of every part in the circuit, and then the design requirements of each part can be given. Compared with the calculation method using turn-on waveform of double-pulse experiment, the results show that the proposed method meets positive design principle and has faster computing speed.